CLINICAL AND PATHOGENETIC ASPECTS OF TOPICAL IMMUNOMODULATOR USAGE IN CHILDREN WITH OTORHINOLARYNGOLOCAL DISEASES - S. A. Ivanichkin (Вопросы современной педиатрии)
The article contains the review of modern studies performed by the leading Russian and foreign researchers, dealing with different aspects of topical immunomodulators usage in prophylaxis and treatment of the most common viral and bacterial otorhinolaryngological diseases in children. The review covers the pathogenetic and etiological bases of usage of these drugs and peculiarities of child’s immune system, awareness of which explains the reasonability of including of topical immunomodulators into prophylaxis and treatment of such conditions. The author analyzed the typical mistakes in management of patients with aforesaid diseases and frequently ill children, consequences of these mistakes and possibilities of their avoidance with the help of immunomodulators usage.